Bagaimana Variabel Makroekonomi Mempengaruhi Pengangguran - Ardhia Pramesti Wigayanthi; Dini Yuniarti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In Indonesia, unemployment is a very serious macroeconomic problem influenced by various interrelated economic variables. The purpose of this study is to examine how poverty, exchange rates, inflation, and GDP impact unemployment in Indonesia during the period 1984–2024. Vector Autoregression (VAR) using annual time series data obtained from the World Bank. The results show that, although poverty does not have a significant impact, inflation and the exchange rate do have a direct impact on unemployment in the short term. In addition, this study found that there is a bidirectional relationship between GDP and poverty. Overall, these results indicate that this study can broaden the understanding of structural problems in the labor market and provide analysis for the formulation of more targeted macroeconomic policies.